Assessment of Camel Production and Husbandry Practices in Degahbour District, Jarar Zone, Somali Regional State, Ethiopia - Abdimahad, Kownin; Abdilahi, Abdi; Mahamed, Abdulahi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The study was conducted in Degahbur district of the Somali Regional State to generate baseline information on camel production and husbandry practices. Data were collected from four purposively selected kebeles based on camel population and production potential. Using semi-structured questionnaires, focus group discussions, and field observations, 200 households (120 pastoral and 80 agropastoral) were interviewed. Results indicated that the majority of respondents were male (85%) and middle-aged (58%), with a high illiteracy rate (73%), significantly higher among pastoralists (p = 0.002). Pastoralists owned larger camel herds (6.12 ± 0.78) compared to agropastoralists (p < 0.001). Men predominantly performed activities such as feeding (80%), herding (90%), milking (95%), and treating camels (95%), while women were primarily responsible for selling camel milk (85%) and barn cleaning (85%). The main purposes of camel keeping were milk production and income generation. Browsing trees and shrubs were the primary feed resource during the dry season (64%), and wells served as the main water source (62%). Major constraints identified were feed shortages (0.240 & 0.260), recurrent drought (0.222 & 0.231), and animal diseases (0.172 & 0.160) for both production systems. Key opportunities included increasing demand for camel products, multipurpose use of camels, their high adaptability, and cultural significance. Camel production remains vital for local livelihoods but faces significant challenges, particularly in feed and water availability, warranting strategic interventions. Strengthening integrated support systems including improved feed and water management, veterinary services, and market access is essential to enhance camel production and pastoral and agropastoral livelihoods in the area.